A VIKOR-based approach to evaluate river contamination risks caused by wastewater treatment plant discharges. (1st November 2022) - Atangana Njock, Pierre Guy; Shen, Shui-Long; Zhou, Annan; Lin, Song-Shun
Highlights: An approach enhances management of WWTPs-induced river contamination. An index is defined to characterize risk status level of treatment plants cluster. The approach is applied to a cluster of treatment plants along the Pearl River. Performance of the proposed model is compared with TOPSIS. Abstract: Wastewater treatment plants (WWTPs) rarely eliminate emerging contaminants from effluents they discharged into waterways, and therefore, represent significant contaminations sources with deleterious environmental risks. This paper presents a VIKOR-based model to assess the contamination risk posed by a cluster of WWTPs. A risk index was defined via building a membership function embodying the performance degrees of WWTPs and risks levels within the framework of fuzzy set theory. The proposed approach was tested using a case study of WWTPs cluster along the Pearl River. Sensitivity analyses were carried out to investigate the robustness of the model. The results confirmed the ability of the proposed approach to reveal the risk level of a given treatment point. Further, the comparison with a TOPSIS scheme as well as sensitivity analysis results substantiate the consistency, accuracy, and reliability of the proposed approach. It is therefore bounds to improve the decentralized management of WWTPs-induced river contamination. Graphical abstract: Image, graphical abstract